Kemampuan Laba Fiskal Memprediksi Pertumbuhan Laba - Putri, Anne (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2009)
The objective of this research is to test the capacity of fiscal profit prediction. This research propose the following Hypotheses. Fiscal profit many predict the profit improvement. In order to tests that of Hypotheses, the linear regression models developed. The dependent variable is fiscal profit estimated by ratio between fiscal profit and accounting net profit. While the independent variable is profit improvement that spesified onto the nest one year, three years, and five years profit improvement. Meanwhile, the control variables are company's beta, PER, PBV, and SIZE. Thoose model parameters eestimated with the data pooling of regression estimation of common effect and GLS method, under the use of data that consists of 55 manufacturing companies registered in Indonesia stock Exchange during the 2002-2007 period year. The result shows that all of the empirical models are significant. The output of the test presents that empirical evidence supports the proposed Yhpotheses, that is fiscal profit may predict profit improvement for until the next three years. That can be concluding generally that fiscal profit has a predictive content.